PERUBAHAN TIPOLOGI FASAD PADA RUMAH TRADISIONAL KAMPUNG PITU GUNUNG KIDUL - Dwiani Intan Kartika Putri (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: This Village unique and sacred research began to be introduced in 2015, the uniqueness of the settlement appeared in the combination of customs and traditions that were maintained authenticity with the indigenous people of Pitu Village. This affects change in the facade settlenet past and present seen from the Architectural aspects in the Pitu Village settlement, one of which is through the condition of houses there. The purpose of this study is to determine the typology of the traditional facade of Pitu Village with cultural elements and indirect communication between humans as a traditional the collection of research data is. This study uses a qualitative descriptive method The collection of research data was the result of interviews and observations at the research site with seven houses in Pitu Village. The changes of traditional houses typical of Pitu Village as a result of community planning into Vernacular Architecture is rated from the peculiarities of cultural aspects, building philosophy, of the village and one of the peculiarities of the community's house. This is considered to know the peculiarities in the area, especially the façade at Pitu Village residential house in applying the Vernacular Architecture Concept to the building style, it is necessary to analyze it with a comparative form before and after in the location of the area, the façade of the Pitu Village residential house by finding out the characteristics of the local Vernacular Architecture and the Characteristics of Ventakular Architecture with the points and shapes of the façade in the building planned in Pitu Village. The conclusions in this study reveal the development of an approach at the concept of vernacular traditional architecture into a modern livable house concept.Abstrak: Penelitian perkampungan Unik dan sakral mulai diperkenalkan pada tahun 2015, keunikan permukiman muncul dalam perpaduan adat dan tradisi yang terjaga keasliannya dengan warga asli Kampung Pitu. hal ini berpengaruh terhadap adanya perubahan permukiman fasad rumah dahulu dan fasad rumah sekarang di lihat dari Aspek Arsitektural permukiman Kampung Pitu, salah satunya melalui kondisi rumah. Tujuan penelitian ini untuk mengetahui tipologi fasad tradisional Kampung Pitu dengan unsur kebudayaan dan komunikasi tidak langsung antar manusia sebagai perancang rumah tradisional di kawasan Kampung Pitu. Penelitian ini menggunakan metode deskriptif kualitatif, pengumpulan data penelitian merupakan hasil dari wawancara dan pengamatan di lokasi penelitian bersama tujuh masyarakat asli Kampung Pitu. Perubahan rumah tradisional khas Kampung Pitu hasil dari perencanaan masyarakat menjadi Arsitektur Vernakular dinilai dari kekhasan segi budaya, filosofi bangunan salah satu kekhasan pada rumah masyarakatnya. Hal tersebut dipandang memiliki potensi desa, kekhasakan kawasan terutama fasad rumah tinggal Kampung Pitu dalam menerapkan Konsep Arsitektur Vernakular terhadap gaya bangunan, maka perlu adanya analisis dengan bentuk perbandingan sebelum dan sesudah fasad rumah tinggal Kampung Pitu dengan mencari tau ciri Arsitektur Vernakular setempat dan dengan adanya poin dan bentuk secara fasad dalam bangunan yang direncanakan. Penelitian ini mengungkapkan pengembangan sebuah pendekatan konsep Arsitektur tradisonal Vernakular menjadi konsep rumah modern layak huni.